2003
DOI: 10.1002/ejic.200390214
|View full text |Cite
|
Sign up to set email alerts
|

Mn and Fe K‐edge XAS Spectra of Manganese and Iron Nitrido Compounds

Abstract: We performed a Mn K-edge XAFS study of a number of highly moisture-sensitive nitridomanganates with manganese in different oxidation states and in various surroundings: [x = 0.26(1)] were measured. The energy positions of the pre-edge maxima are almost independent of the electronic state of Mn, while the intensity is sensitive to the geometric arrangement of the coordination of Mn. The mainedge is sensitive to the oxidation state − a clear shift to higher energies with increasing oxidation state can be seen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
1
19
1
Order By: Relevance
“…It has been found that T = Mn, Fe, Co, Ni, and Cu can be substituted for one of the Li-sites: the two-fold coordinated 1b Wyckoff site. Indications for an unusual oxidation state of +1 were also reported 2,[5][6][7]14 . The transition metals carry a sizable local magnetic moment except for T = Cu and highly concentrated T = Ni 5,7,8 .…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…It has been found that T = Mn, Fe, Co, Ni, and Cu can be substituted for one of the Li-sites: the two-fold coordinated 1b Wyckoff site. Indications for an unusual oxidation state of +1 were also reported 2,[5][6][7]14 . The transition metals carry a sizable local magnetic moment except for T = Cu and highly concentrated T = Ni 5,7,8 .…”
mentioning
confidence: 71%
“…With an estimated MAE of several hundred Kelvin and, in accordance, an observed coercivity field of more than 11 Tesla this compound exceeds even the largest values observed in rare-earth based permanent magnets. Besides iron, other 3d transition metal substitutions were synthesized, in polycrystalline form, as early as 1949 by Sachsze and Juza 2 and have been subjects of ongoing experimental [3][4][5][6][7][8][9][10] and theoretical investigations [11][12][13] . It has been found that T = Mn, Fe, Co, Ni, and Cu can be substituted for one of the Li-sites: the two-fold coordinated 1b Wyckoff site.…”
mentioning
confidence: 99%
“…5). Both nitridocobaltates show a good separation of the pre-edge ARTICLE IN PRESS feature (at about 7713 eV) with the pre-edge peaks assigned to a 1s-3d transition [32], as expected for a noncentrosymmetric environment of Co. The main absorption edge reflects the 1s-4p transition; the shift of the main absorption edge at 0.6 of the total edge jump was employed to assign the oxidation states of Co with higher energies being associated with an increase in oxidation states.…”
Section: Resultsmentioning
confidence: 99%
“…Some weak pre-edge features (1s → 3d transition [10,11]) appearing as a shoulder of the main edge for all the nitridocobaltates at ∼7713 eV, are also observed. As expected, the Co K-edges of nitridocobaltates(I) are located at lower energy (shift ≈ 4 eV) in comparison with Co 3 O 4 which contains Co II/III .…”
Section: Discussionmentioning
confidence: 83%
“…According to literature data [10] the energy at the main edge at about 0.6 of the normalized absorption as well as the pre-edge peak positions are usually considered for oxidation state assignments of the transition metals. Some weak pre-edge features (1s → 3d transition [10,11]) appearing as a shoulder of the main edge for all the nitridocobaltates at ∼7713 eV, are also observed.…”
Section: Discussionmentioning
confidence: 99%